The effect of aromatherapy on quality of sleep in pre-post-menopausal women: A systematic review and meta-analysis - Mona Najaf Najafi; Salmeh Dadgar; Masumeh Ghazanfarpour (Mashhad University of Medical Sciences, 2018)
Introduction: One of the most common problems in postmenopausal women is sleep disorders. This disorder can be manifested by mild to severe symptoms of discomfort in different people. One of the approaches to relieve sleep disorders is the use of complementary medicine, including aromatherapy. This systematic review and meta-analysis was conducted with the aim to evaluate and summarize the results of clinical trials on the effects of aromatherapy in premenopausal and postmenopausal women with sleep disorders. Methods: Latin databases such as PubMed, Scopus, ISI Web of Science, Cochrane Library, and Persian databases such as SID and magiran were systematically searched until 10 February 2018 without time limitation. The Jadad scale was used to evaluate the quality of the articles. Sleep duration or sleep quality was considered as the main outcome of the study. Results: Among 4 found studies, Lavender essence was used for aromatherapy alone or in combination with other methods or fragrances. The results of the meta-analysis on three studies which had reported the quality of sleep showed that the standardized mean difference between intervention and control groups was 1.338 (95% CI: 0.329-2.347); this difference shows sleep quality score was improved in the intervention group compared to the control group (p = 0.009). In one study which had reported the sleep time of samples, there was no significant difference between intervention and control groups in sleep hours (p = 0.373). Conclusion:Lavender essence aromatherapy alone or in combination with other methods can have beneficial effects on improving the sleep quality in pre and postmenopausal women